Natural resources, neither curse nor destiny - Lederman, Daniel, 1968-; Maloney, William F. (William Francis), 1959- (Latin American development forum., 2007)
This volume studies the role of natural resources in development and economic diversification. It brings together a variety of analytical perspectives, ranging from econometric analyses of economic growth to historical studies of successful development experiences in countries with abundant natural resources.